The elements we live by : how iron helps us breathe, potassium lets us see, and other surprising superpowers of the periodic table - Røyne, Anja (The Experiment, 2020)
"A journey through chemistry and physics introducing the elemental building blocks from which humans are made--iron, phosphorus, silicon, potassium, and more"--